1995
DOI: 10.1017/s0031182000064805
|View full text |Cite
|
Sign up to set email alerts
|

Proteinases releasedin vitroby the parasitic stages ofTeladorsagia circumcincta, an ovine abomasal nematode

Abstract: Proteinases released during in vitro maintenance of third (L3) and fourth larval stage (L4) and adult Teladorsagia circumcincta (formerly Ostertagia circumcincta), an ovine abomasal nematode parasite, were characterized on the basis of pH optima, molecular size and specific proteinase inhibitor sensitivity. Enzyme activity was maximal at alkaline pH and stage-specific release was demonstrated. Proteinases released by the adult parasite degraded a variety of protein substrates including plasminogen, albumin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…At 14 dpi, AB-PAS and HID-AB stainings showed that the abomasal mucosa was characterized by depletion of both neutral and acidic mucins, confined to the area invaded by the parasite larvae, indicating a strictly localized response to the parasite. The limited modification observed at this stage of the infection may be an attempt of the parasite to create an optimal environment for itself through the production of enzymes that break down mucin protein and carbohydrate structures, as previously suggested [33]. In the rest of the mucosa, during the infection, the alteration in mucin composition, in particular in the hyperplastic glands, was characterized by a decrease of neutral and an increase in acidic mucins produced by the MNCs in the neck region of the gland.…”
Section: Discussionmentioning
confidence: 83%
“…At 14 dpi, AB-PAS and HID-AB stainings showed that the abomasal mucosa was characterized by depletion of both neutral and acidic mucins, confined to the area invaded by the parasite larvae, indicating a strictly localized response to the parasite. The limited modification observed at this stage of the infection may be an attempt of the parasite to create an optimal environment for itself through the production of enzymes that break down mucin protein and carbohydrate structures, as previously suggested [33]. In the rest of the mucosa, during the infection, the alteration in mucin composition, in particular in the hyperplastic glands, was characterized by a decrease of neutral and an increase in acidic mucins produced by the MNCs in the neck region of the gland.…”
Section: Discussionmentioning
confidence: 83%
“…The relative proteinase activity present in extracts from parasites has been shown to vary considerably, depending on the protein substrate used for analysis (Maki and Yanagisawa 1986;Knox and Jones 1990;Young et al 1995) as well as the medium used for isolation or for determination of the activity. The present investigation shows that the presence of phosphates in the incubation medium (which are very often used) may influence the activity of various proteinases, thus making a comparison of the values recorded among various laboratories difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlation between pathogenicity and proteinase parasite activity has been reported for nematodes such as Dirofilaria immitis (Tamashiro et al 1987), Nematospiroides dubius (Monroy et al 1989), Strongyloides stercoralis , Anisakis simplex (Sakanari and McKerrow 1990), Necator americanus (Kumar and Pritchard 1992;Brown et al 1995), Onchocerca spp. (Lackey et al 1989;Lustigman 1993), Trichinella spiralis Gimenez-Pardo et al 1992), Trichuris muris (Drake et al 1994), Strongylus vulgaris (Caffrey and Ryan 1994), Ancylostoma caninum (Harrop et al 1995;Hawdon et al 1995) and Teladorsagia (Ostertagia) circumcincta (Young et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Their presumed functions such as nutrition uptake, tissue penetration and evasion of host immune responses emphasize their importance as targets for helminth control [13, 23, 26, 33, 39]. …”
Section: Introductionmentioning
confidence: 99%